2012
DOI: 10.1016/j.jspi.2011.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Accounting for uncertainty in heteroscedasticity in nonlinear regression

Abstract: Toxicologists and pharmacologists often describe toxicity of a chemical using parameters of a nonlinear regression model. Thus estimation of parameters of a nonlinear regression model is an important problem. The estimates of the parameters and their uncertainty estimates depend upon the underlying error variance structure in the model. Typically, a priori the researcher would know if the error variances are homoscedastic (i.e., constant across dose) or if they are heteroscedastic (i.e., the variance is a func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 21 publications
0
24
0
1
Order By: Relevance
“…However, ranking substances based on AC 50 estimates derived from fits to the Hill Equation was always resulted in poor performance. Other studies have demonstrated that the Hill Equation model parameters can be unreliable estimates due to large variations in observed responses at higher doses, irregular dose spacing or data collected over an incomplete dose range 5,8,31 . In contrast to AC 50 , WES is based strictly on the observed responses and never relies on estimates of the behavior of a nonlinear function outside of the tested concentration range.…”
Section: Discussionmentioning
confidence: 99%
“…However, ranking substances based on AC 50 estimates derived from fits to the Hill Equation was always resulted in poor performance. Other studies have demonstrated that the Hill Equation model parameters can be unreliable estimates due to large variations in observed responses at higher doses, irregular dose spacing or data collected over an incomplete dose range 5,8,31 . In contrast to AC 50 , WES is based strictly on the observed responses and never relies on estimates of the behavior of a nonlinear function outside of the tested concentration range.…”
Section: Discussionmentioning
confidence: 99%
“…The above test statistic can be approximated as L OLSE = { η̂ t ( Ĥ−H 0 ) η̂ /3}/{ η̂ t ( I n − Ĥ ) η̂ /( n −4)}+ o P (1) = L OLSE + o P (1), where η̂ = Y − β̂ 1 , Y = ( y 11 ,…, y k,n k ) t , β̂ = ȳ , 1 = (1,…, 1) t , Ĥ = F̂ ( F̂ t F̂ ) −1 F̂ t , F̂ = f θ ( θ̂ ) = { ∂f ( x i , θ )/ ∂θ j ∣ θ=θ̂ }, and H 0 = 1 ( 1 t 1 ) −1 1 t . Since L OLSE is not robust to outliers and influential observations, in this paper we make it robust by replacing OLSE by OME θ̃ n , in the above calculations, where OME is defined as (Lim et al 2012): θ̃ n = Argmin {Σ i,j h 2 ( y ij − f ( x i , θ )) : θ ∈ ℜ p } where h is taken to be the Huber-score function. For a pre-specified positive constant k 0 , h(u)=u/2, if | u | < k 0 , otherwise h ( u ) = { k 0 (| u |− k 0 /2)} 1/2 .…”
Section: Methodsmentioning
confidence: 99%
“…We shall denote the resulting statistic by L OME . Since OME and OLSE are asymptotically equivalent and OME is consistent and asymptotically normally distributed (Lim et al 2012), the null distribution of L OME can also be approximated by central F -distribution with (3, n − 4) degrees of freedom. Throughout this paper we shall refer to this modified LRT as the OME based methodology.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, as with a number of key technologies, in practical applications the performance of incremental localization techniques still faces many technical problems, of which the most deadly one is the error accumulation problem, that a prior localization error affects the next locating performance, and the influence is cumulative. The accumulation of the errors will inevitably lead to the difference between the variance of the previous locating error and the variance of the posterior locating error, which is known as heteroscedasticity [5,13]. If heteroskedasticity appears in the process of locating and estimating, the location estimation of the unknown nodes using the OLS may not be efficient estimators, nor even asymptotically efficient estimators.…”
mentioning
confidence: 99%